Implementation of an extension project in educational robotics in a public school: A case study in the city of Natal/RN - Dantas, Igor M. L.; Alves, Karina M. S.; Silva, Maria Da G. T. Da; S. Junior, Orivaldo V.; Gonçalves, Luiz M. G. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
This article describes the experience of an extension project with public school students in Natal/RN, to train them for the SESI Robotics Tournament, regional stage 2002/2023. The project arose in educational robotics classes with primary school classes in Geography. The method used was a case study with empirical observation of the students' learning process and the application of questionnaires. The overall aim of this research was to understand how educational robotics can help students to develop new skills and competences combined with a pedagogical proposal. The specific objectives are: 1. To analyze the students' potential in the field of robotics, 2. To prepare them for robotics tournaments, 3. To investigate new approaches to using educational robotics with students with disabilities, 4. To study new possibilities in the field of educational robotics using recyclable materials. The results were positive, with the students developing the skills and competencies inherent in educational robotics and broadening their learning. Robotics also proved to be an excellent teaching tool for the inclusion of students with disabilities or learning disorders. The article concludes that successful initiatives such as this show the possibility of creating spaces for discussion and dialogue with public authorities in order to overcome difficulties and strengthen the possibility of creating draft laws establishing robotics as a compulsory subject in the public school system.